2008
DOI: 10.1007/s00424-008-0517-2
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 2 regulates the active uptake of the organic osmolyte taurine in NIH3T3 mouse fibroblasts

Abstract: Inhibition of the constitutively active casein kinase 2 (CK2) with 2-dimethyl-amino-4,5,6,7-tetrabromo-1H-benzimidasole stimulates the Na(+)-dependent taurine influx via the taurine transporter TauT in NIH3T3 cells. CK2 inhibition reduces the TauT mRNA level and increases the localization of TauT to ER but has no detectable effect on TauT protein expression. On the other hand, CK2 inhibition increases the affinity of TauT towards Na(+ )and reduces the Na(+)/taurine stoichiometry for active taurine uptake. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Mammalian TauT show a 90% sequence identity and it appears that several TauT isoforms occur in e.g. mouse fibroblasts, which can be distinguished by their molecular weight in Western blotting analysis [19,42,43] as well as their affinity towards taurine [42] and their Na + :taurine stoichiometry [18] in kinetic analysis. Hydropathy plots indicate that TauT contains 12 transmembrane domains and drawing an analogy with the structure of other members of the Na + -Cl --coupled SLC6 transporter family and the leucine transporter for leucine from Aquifex aeolicus (LeuTAa) [44,45] it is revealed that the binding pockets for Na + and taurine in TauT are coordinated by residues on TM1, TM3, TM6 and TM8 and that variation in Na + :taurine stoichiometry reflect variation in Na + binding sites [44].…”
Section: Taurine Uptake -Tautmentioning
confidence: 99%
See 2 more Smart Citations
“…Mammalian TauT show a 90% sequence identity and it appears that several TauT isoforms occur in e.g. mouse fibroblasts, which can be distinguished by their molecular weight in Western blotting analysis [19,42,43] as well as their affinity towards taurine [42] and their Na + :taurine stoichiometry [18] in kinetic analysis. Hydropathy plots indicate that TauT contains 12 transmembrane domains and drawing an analogy with the structure of other members of the Na + -Cl --coupled SLC6 transporter family and the leucine transporter for leucine from Aquifex aeolicus (LeuTAa) [44,45] it is revealed that the binding pockets for Na + and taurine in TauT are coordinated by residues on TM1, TM3, TM6 and TM8 and that variation in Na + :taurine stoichiometry reflect variation in Na + binding sites [44].…”
Section: Taurine Uptake -Tautmentioning
confidence: 99%
“…The TauT promoter contains DNA consensus binding sites for the zinc finger-containing transcription factors Sp1 (required for basal promoter activation), TG repeats (critical for full expression of TauT), binding site for the Wilms tumor suppressor (WT1, required for enhanced TauT transport activity), a tonicityenhancer element (TonE, required for hypertonicityinduced upregulation of TauT transcription), a consensus binding site for the transcriptional regulator p53 (p53 binding suppresses TauT transcription) as well as a putative taurine response element (involved in taurininduced downregulation of TauT transcription) [55,56]. CK2 targets Sp1, p53, topoisomerase, RNA polymerase as well as the TonE binding protein (see [57,58]) and it has been demonstrated that inhibition of CK2 reduce TonEBP activity [58] and prevents hypertonicity-induced upregulation of TauT transcription in NIH3T3 cells [19]. At the same time alters the subcellular TauT localization, i.e., from being evenly distributed in control cells TauT localizes at the endoplasmatic reticulum following CK2 inhibition [19].…”
Section: Taut Regulation Long-termmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular taurine content is generally a balance between active uptake via the Na ϩ -and Cl Ϫ -dependent taurine transporter (TauT), passive release via volume-sensitive and volume-insensitive transporters (28), and in some cells (liver, pancreas, and testis) synthesis from cystein/methionine (31). Acute modulation of TauT activity involves Ser/Thr kinases (PKA, PKC, and CK2) and reactive oxygen species (ROS) (12,13,22,31,40,41,63), whereas long-term regulation of TauT activity involves transcriptional regulation by cellular osmo-sensing proteins (TonEBP, tonicity end-binding protein) and amino-sensing kinases (mTOR, mammalian target of rapamycin) (9,27,30,31). In contrast to the active taurine uptake system involving TauT, taurine release involves 1) volume-sensitive leak pathways, activated by osmotic cell swelling [termed the volumesensitive organic anion channel (VSOAC)]; and 2) volumeinsensitive leak pathways, activated during anoxia, apoptosis, and cholesterol depletion (27,31,45,61).…”
mentioning
confidence: 99%
“…The total body pool is controlled by renal taurine retention via TauT located at the proximal tubule and distal nephron. Translocation of one taurine molecule across the plasma membrane via TauT involves two to three Na ions and acute modulation of TauT activity by protein kinases (PKA, PKC, CK2) and ROS involves shift in TauT's substrate affinity, transport capacity, and/or the Na:taurine stoichiometry (13,14,19,45,69). Passive taurine release from cells via VSOAC activation involves 1) mobilization of arachidonic acid from the nuclear envelope by cell-specific PLA 2 subtypes (52,53), ROS generation by NADPH oxidases (8,34), and fatty acid oxidation to leukotrienes by 5-lipoxygenase (5-LO) (38); 2) increased tyrosine kinase activity (34,51); and 3) activation of protein kinases normally related to growth factor signaling, i.e., phosphatidylinositol 3-kinase (PI3K), Akt, and glycogen synthase kinase 3␤ (GSK3␤) (36).…”
mentioning
confidence: 99%